Pengaruh Peningkatan Kemampuan Personil, Pengenalan Keselamatan, dan Sosialisasi Kawasan Keselamatan Operasi Penerbangan terhadap Kualitas Individu pada Pelayanan Jasa Kebandarudaraan - Tiara Nugrahayani; Rifqi Raza Bunahri (Dinasti Review, 2022)
The utilization of airspace is the implementation and sovereignty of the Republic of Indonesia as a whole. Including the national airspace arrangement, service delivery, personnels, facilities, flight navigation services, and the imposition of sanctions in accordance with applicable legal regulations in Indonesia. Airports are the most important facilities in air transportation services in various places including in Indonesia, because their function is intended as a place for departure and landing of aircraft, boarding and falling of passengers, goods (cargo), and postal. The method of writing this scientific article is to apply qualitative methods and methods of literature. This study uses the literature review method so as to obtain results on Personnels Capability has an influence on Individual Quality in Airport Services, Safety recognition has an influence on Individual Quality in Airport Services, and Socialization of Safety Areas has an influence on Individual Quality in Airport Services.